Susan L. answered • 10/12/12

Everyone CAN get it! Math isn't hard when it's explained right.

So you have 12 + 3(2y-3)

simplify typically means to 'combine like terms'

in order to do that in this problem, you need to 'distribute' the 3(2y-3)

12 + 3(2y - 3)

12 + (3*2y) + (3*-3) --> distribute the 3 across the members inside the parenthesis

12 + 6y -9 --> perform the math inside the parenthesis first

NOW we combine like terms

12 - 9 + 6y --> since addition is commutative, order does NOT matter -- we are allowed to

move things around to make easier

3 + 6y --> this is the fully 'simplified' answer

You can then factor out a 3 -- this gives you your 'factored' answer

3(1+2y) --> the key to factoring is to 'distribute' your factored answer and make sure you get back to the

correct value

Distribution of 3(1+2y) = (3*1) + (3*2y) = 3 + 6y CORRECT!!